Assessing quality of life in older horses. (2nd September 2020) - Ireland, Jo
Abstract : The equine population is ageing and equine geriatric medicine is a growing field. With increasing horse age, both the frequency of veterinary attention and the provision of several preventive health care measures are reduced. Moreover, owners appear to under-recognise several prevalent age-associated diseases, often considering clinical signs as normal signs of ageing. There is a high burden of chronic disease within the geriatric equine population, which may have a detrimental effect on quality of life. In the absence of a validated equine quality of life measurement scale, this review highlights factors and domains that should be evaluated in a comprehensive assessment of the quality of life in older horses. The potential benefits of assessing quality of life as a routine component of veterinary care for older horses are also summarised.